Review of organizational value of science-intensive organizations configuration models (rocket and space industry organization case) - V. А. Shiboldenkov; S. S. Gavrilov (Вестник университета, 2023)
The article studies main models for compiling organizational cost of scientific-intensive enterprises used in rocket and space industry. Practical application of the most important value configurations analysis has been carried out, as well as analysis of economic activity. The implementation potential of the most promising algorithms of value creation in knowledge-intensive enterprises of the Russian Federation has been assessed. The “Introduction” describes the latest trends in intangible asset management development. The “Research Methods” describes three configurations of value creation (chain, workshop, network) in detail. The “Research Results” describes current architecture of Roscosmos (Porter value chain and Osterwalder business model). In conclusion, the results of the work done have been summarized: relevance of these tools application and what model is best for Roscosmos to move to.